2015
DOI: 10.1007/s11259-015-9631-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of opioid-induced feeding behavior by endogenous nitric oxide in neonatal layer-type chicks

Abstract: The current study was designed to evaluate the effects of central administration of L-arginine (The precursor of nitric oxide), N(G)-nitro-L-arginine methyl ester (L-NAME), a nitric oxide (NO) synthase inhibitor, selective opioid receptor agonists and involvement of central nitrergic/opioidergic systems on feeding behavior in neonatal layer-type chicks. The results of this study showed that the intracerebroventricular (ICV) injection of L-arginine (400 and 800 nmol) significantly decreased food intake (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…For example, NO is involved in the hypothermia, catalepsy and anxiogenic or anxiolytic effects induced by CB 1 receptor agonists (Roohbakhsh et al, 2007). Central food intake regulation is a complex phenomenon, a diversity of neurotransmitters acts via a complex neurological pathway in several nucleuses of the CNS and co-operate together to regulate feed intake in animals (Zendehdel et al, 2014b;Alimohammadi et al, 2015). Within the hypothalamus CB 1 receptors expressed within the pre-synaptic nerve terminals of the ARC, PVN, ventromedial and lateral hypothalamus (Wittmann et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, NO is involved in the hypothermia, catalepsy and anxiogenic or anxiolytic effects induced by CB 1 receptor agonists (Roohbakhsh et al, 2007). Central food intake regulation is a complex phenomenon, a diversity of neurotransmitters acts via a complex neurological pathway in several nucleuses of the CNS and co-operate together to regulate feed intake in animals (Zendehdel et al, 2014b;Alimohammadi et al, 2015). Within the hypothalamus CB 1 receptors expressed within the pre-synaptic nerve terminals of the ARC, PVN, ventromedial and lateral hypothalamus (Wittmann et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In each group, 12 birds received the injection, but just data of those individuals where the dye was present in their lateral ventricle (12 chickens per group), was used for the analysis. All experimental procedures were done from 8:00 A.M. until 3:30 P.M. Also, the time course for feeding behavior was selected by previous studies (Jonaidi et al, 2012;Zendehdel & Hassanpour 2014;Alimohammadi et al, 2015;Alizadeh et al, 2015;Hassanpour et al, 2015).…”
Section: Involvement Of Gaba and Cannabinoid Receptors In Central Foomentioning
confidence: 99%
“…After injection, the chick was immediately returned to its cage and fresh food and water were supplied. Cumulative food intake (gr) was measured at 30, 60 and 120 min after the injection and the time course of food consumption was selected from previous studies (Alimohammadi et al 2015;Jonaidi et al 2012). Food consumption was expressed as a percentage of body weight to adjust body weight differences.…”
Section: Icv Injectionmentioning
confidence: 99%
“…Numerous studies over the past several decades have shown that complex neurochemical pathways in different parts of the brain regulate appetite and food intake in animals (Alimohammadi et al 2015). Nitric oxide (NO) is a gaseous neurotransmitter in the brain and is made from l-arginine by nitric oxide synthase (NOS) (Morris 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation